BIRC5/Survivin is a novel ATG12–ATG5 conjugate interactor and an autophagy-induced DNA damage suppressor in human cancer and mouse embryonic fibroblast cells. Issue 7 (2nd July 2020) - Lin, Tzu-Yu; Chan, Hsiu-Han; Chen, Shang-Hung; Sarvagalla, Sailu; Chen, Pai-Sheng; Coumar, Mohane Selvaraj; Cheng, Siao Muk; Chang, Yung-Chieh; Lin, Chun-Hui; Leung, Euphemia; Cheung, Chun Hei Antonio
ABSTRACT: BIRC5/Survivin is known as a dual cellular functions protein that directly regulates both apoptosis and mitosis in embryonic cells during embryogenesis and in cancer cells during tumorigenesis and tumor metastasis. However, BIRC5 has seldom been demonstrated as a direct macroautophagy/autophagy regulator in cells. ATG7 expression and ATG12–ATG5-ATG16L1 complex formation are crucial for the phagophore elongation during autophagy in mammalian cells. In this study, we observed that the protein expression levels of BIRC5 and ATG7 were inversely correlated, whereas the expression levels of BIRC5 and SQSTM1/p62 were positively correlated in normal breast tissues and tumor tissues. Mechanistically, we found that BIRC5 negatively modulates the protein stability of ATG7 and physically binds to the ATG12–ATG5 conjugate, preventing the formation of the ATG12–ATG5-ATG16L1 protein complex in human cancer (MDA-MB-231, MCF7, and A549) and mouse embryonic fibroblast (MEF) cells. We also observed a concurrent physical dissociation between BIRC5 and ATG12–ATG5 (but not CASP3/caspase-3) and upregulation of autophagy in MDA-MB-231 and A549 cells under serum-deprived conditions. Importantly, despite the fact that upregulation of autophagy is widely thought to promote DNA repair in cells under genotoxic stress, we found that BIRC5 maintains DNA integrity through autophagy negative-modulations in both human cancer and MEF cells under non-stressed conditions. In conclusion, our study reveals a novel role of BIRC5 in cancer cells as a direct regulator of autophagy. BIRC5 may act as a "bridging molecule", which regulates the interplay between mitosis, apoptosis, and autophagy in embryonic and cancer cells. Abbreviations: ACTA1: actin; ATG: autophagy related; BIRC: baculoviral inhibitor of apoptosis repeat-containing; BAF: bafilomycin A1 ; CQ: chloroquine; CASP3: caspase 3; HSPB1/Hsp27: heat shock protein family B (small) member 1/heat shock protein 27; IAPs: inhibitors of apoptosis proteins; IP: immunoprecipitation; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; PLA: proximity ligation assay; SQSTM1/p62: sequestosome 1; siRNA: small interfering RNA